Overview on field evaluation of three insecticides for control of the black pepper / Sang Jam - Jam, Sang (2015)
Malaysian Pepper Board (MPB) has registered Sarawak Pepper with the Intellectual Property Corporation of Malaysia (MylPO) as a product under Geographical Indications (Gl) since 4th November 2003 as per stipulations in the Certification of Registration under the Geographical Indications Act 2000, Geographical Indication Regulations 2001. Among the objectives of Gl registration for Sarawak Pepper is primarily to protect the name, image and reputation such as the unique flavor profile, quality reputation, consumer loyalty and price premium either locally or abroad. It provides protection for Sarawak Pepper in any form, all graded pepper, value added pepper products and pepper based products of Malaysia from being illegally exploited by others.